2002
DOI: 10.1097/00004872-200202000-00019
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of human vascular smooth muscle extracellular matrix protein production by α- and β-adrenoceptor stimulation

Abstract: These results uniquely demonstrate the capacity for adrenergic stimulation to directly modulate TGFbeta1 expression and ECM protein synthesis by the human cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 31 publications
1
33
0
1
Order By: Relevance
“…They show that eutrophic (collagen deposition and fibrosis) and hypertrophic (proliferation and migration of smooth muscle cells and of adventitial fibroblasts) remodelling characterizes the damages caused by catecholamines on the vascular wall (1,(4)(5)(6)(7)(8)(9). These observations have also been indirectly confirmed by using a-adrenoceptor antagonists (9)(10)(11)(12)(13) and by experiments in animals submitted to local or systemic sympathetic denervation (14).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…They show that eutrophic (collagen deposition and fibrosis) and hypertrophic (proliferation and migration of smooth muscle cells and of adventitial fibroblasts) remodelling characterizes the damages caused by catecholamines on the vascular wall (1,(4)(5)(6)(7)(8)(9). These observations have also been indirectly confirmed by using a-adrenoceptor antagonists (9)(10)(11)(12)(13) and by experiments in animals submitted to local or systemic sympathetic denervation (14).…”
Section: Discussionmentioning
confidence: 82%
“…This direct trophic effect of catecholamines, mediated by a-adrenoceptors, concerns an increase in extracellular matrix, with consequent wall fibrosis and eutrophic remodelling. Moreover, in animal models employing balloon injury of the carotid or aorta, an exacerbation of this action may be observed with proliferation, hypertrophy and migration of smooth muscle cells and adventitial fibroblasts, leading to hypertrophic remodelling (1,(4)(5)(6)(7)(8)(9). The direct influence of sympathetic neurotransmitters on vascular wall structure has been supported by studies using a-adrenoceptor antagonists that showed a reduction in proliferation of vascular wall cells and in neointimal growth after vascular injury (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 97%
“…Previous in vitro studies have found that norepinephrine leads to hypertrophy and proliferation of cultured smooth muscle cells 10 and also induces proliferation of adventitial fibroblasts. 8 Norepinephrine-induced hypertrophy of the vascular smooth muscle cells is mediated by a-adrenoceptors, in particular by a 1A,1B and a 1D adrenoceptors.…”
Section: Discussionmentioning
confidence: 91%
“…8 a 1 Adrenoceptors of the smooth muscle cells stimulate production of transforming growth factors b-1, which is involved in vascular hypertrophy, collagen and fibronectin expression. 10,22 Another mechanism, which can lead to the more pronounced thickening of carotid intima-media in subjects with pheochromocytoma, is subclinical inflammation. In our earlier study, we showed an increase of inflammatory markers in subjects with pheochromocytoma compared with patients with other forms of hypertension and normotensive controls, which was reversed by tumour removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation